RETRACTED: Construction Schedule Management for Densely Populated Areas Using CPM-Crashing - Tsulis Iq'bal Khairul Amar; Fresti Febria Astuti; Vivi Tri Wulandari (UKaRsT, 2023)
This article has been retracted: please see U Karst Policy on Article Withdrawal. (https://ojs.unik-kediri.ac.id/index.php/ukarst/article-retraction) This article has been retracted at the request of the Editor-in-Chief. This decision was taken because it was discovered that almost the same article had been published earlier on October 31, 2023, in the Jurnal Teknik Sipil: Rancang Bangun (https://ejournal.um-sorong.ac.id/index.php/rancangbangun/article/view/2632). The author was identified as having made multiple submissions, namely submitting a manuscript in the U Karst Journal on July 3, 2023, and also submitting almost the same manuscript in the Jurnal Teknik Sipil: Rancang Bangun on August 24, 2023. The Editors deplore the practice of simultaneous multiple submissions of papers to different journals. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter, and we apologize to the journal readers that this was not detected during the submission process.